Intertextuality in the Novel (Koykha Swi) by (Aziz Mullah Rash) (Raparin Journal of Humanities (RJH), 2022)
The novel (Kwekha Sewe), which means (Sheikha Siwi), by the creative Kurdish writer and novelist (Aziz Mulla Rash), which was issued and printed in 1986 AD, is considered one of those rare novels at the time that caused gossip and wrote research and articles about it at that time. The reason, as we can see, is due to the fact that it was written and narrated in an easy and simple Kurdish language and an fluent and eloquent Kurdish tongue, which emerged from the depth of its culture and popular heritage which is full of wisdom and sayings of the ancients, in which the Kurdish heritage and folklore were used in a clear and clear way Which is unprecedented in the Kurdish novel, this novel is considered the initiative and the vanguard in this field. The writer (Aziz Mulla Rash), as an original writer with a rich background in the Kurdish folk culture and heritage, benefited greatly in his narration of the novel from the literary elements of folklore, customs and social traditions of the Kurdish community. the novel. With this, the writer was able to accomplish two goals and two aims at the same time, he was able to protect part of the Kurdish folklore and preserve it from damage and loss first, and secondly, he made his narration more coordinated and more tasting.    Therefore, in order to reward the writer for his venerable attempts and generous effort in this regard, we consider it necessary to do this research in this field in honor of his generous effort and the protection and preservation of the Kurdish folk culture and heritage.